A Murky Business. Issue 1 (3rd February 2015) - Jeong, Yujin; Gastwirth, Joseph L.
Abstract: Corruption in Iraq's Oil-for-Food Programme was exposed a decade ago. But key information remains unpublished – information that could shed further light on the impact of bribes paid to Saddam Hussein's regime. By Yujin Jeong and Joseph L. Gastwirth